Trapidil attenuates diabetic cardiomyopathy via GPX3/Nrf2-mediated inhibition of myocardial pyroptosis - Wang, Zihao; Sun, Yingzi; Wang, Juanjuan; Xu, Qiuyue; Wang, Liuxing; Zhang, Qi; Song, Juan; Wang, Yuchun; Qi, Zhanpeng (Frontiers in Pharmacology, 2025)
BackgroundCurrently, there is a paucity of clinically effective medications for the treatment of diabetic cardiomyopathy (DCM), while the strategy of drug repurposing offers a promising avenue for advancing therapeutic development.MethodsThe investigation explored the ameliorative effects and uncovered underlying mechanisms of trapidil (TRA), a drug commonly employed in the management of coronary heart disease, on DCM by inhibiting myocardial pyroptosis. Type 1 DCM models were established utilizing C57BL/6 mice and primary neonatal mouse cardiomyocytes (NMCMs), which were subsequently treated with TRA.ResultsResults demonstrated that in DCM mice, TRA significantly enhanced cardiac function, effectively alleviated pathological changes in myocardial tissue, reversed ultrastructural alterations, and reduced pyroptosome formation in myocardial cells. TRA significantly increased the body weight of the mice in the DCM model group, whereas there was no significant alteration in blood glucose levels following TRA treatment. In the myocardial tissue of DCM mice and high-glucose (HG)-treated NMCMs, TRA was found to correct the aberrant expression of key proteins involved in pyroptosis, including cleaved-caspase1, NLRP3, phospho-NF-κB cyclooxygenase-2, interleukin Cleaved-IL-1β, Cleaved-IL-18, and gasdermin D. Furthermore, TRA effectively curtailed the excessive production of ROS and augmented the mitochondrial membrane potential in NMCMs under the HG environment. Proteomics analysis identified 90 differentially expressed proteins between DCM mice and TRA-treated mice, with glutathione peroxidase 3 (GPX3) emerging as a standout due to its critical role in the cellular antioxidant defense system. Further investigations revealed that the protein and mRNA levels of GPX3, as well as the activated Nrf2 protein levels, were significantly downregulated in the myocardial tissue of DCM mice and HG-treated NMCMs cells. However, these levels were notably upregulated following TRA treatment. Upon knocking down GPX3 mRNA expression using siRNA technology, the anti-pyroptotic effect of TRA in cardiomyocytes was markedly diminished, and the level of activated Nrf2 protein also significantly decreased.ConclusionIn conclusion, TRA holds potential for improving DCM, with the inhibition of myocardial pyroptosis via the GPX3/Nrf2 pathway playing a pivotal role. HG-induced Downregulation of the GPX3/Nrf2 pathway is a critical mechanism underlying pyroptosis in DCM. This pathway can be targeted for the design of DCM-related therapeutics, utilizing the aforementioned signaling mechanisms.